Functional Bracing Following Anterior Cruciate Ligament Reconstruction: A Critical Analysis Review. Issue 9 (September 2021) - Knapik, Derrick M.; Singh, Harsh; Gursoy, Safa; Trasolini, Nicholas A.; Perry, Allison K.; Chahla, Jorge
Abstract : Anterior cruciate ligament (ACL) injuries remain common among athletes; these injuries require reconstruction to restore stability and enable successful return to sport. The role of postoperative dynamic knee bracing following ACL reconstruction in protecting graft integrity and promoting return to sport remains largely unknown. Limited biomechanical studies on functional bracing have reported decreased strain across the ACL with increasing anterior shear loading. Investigations evaluating functional brace use in clinical studies have not yet demonstrated consistent improvement in clinical outcomes, reduced graft retear rates, or improved return-to-sport rates in sports other than skiing. Additional investigation examining athletes of various ages participating in different sporting activities is necessary to better understand the role of functional bracing following ACL reconstruction.